Light triggered formation of photo-responsive epoxy based networks. (27th January 2017) - Radl, Simone; Roppolo, Ignazio; Pölzl, Karina; Ast, Markus; Spreitz, Josef; Griesser, Thomas; Kern, Wolfgang; Schlögl, Sandra; Sangermano, Marco
Abstract: Taking advantage of versatile o -nitrobenzyl chemistry, the present study highlights the design of photocurable epoxy networks that undergo spatially controlled bond cleavage in response to UV irradiation. The synthetic strategy involves the preparation of epoxy monomers with photolabile o -nitrobenzyl ester ( o -NBE) links that are cured via photoinduced cationic ring opening reaction. Two different photoinitiation systems are employed which do not interfere with the absorbance of the o -NBE groups. The first initiation mechanism exploits the direct photolysis of N -hydroxynaphthalimide triflate upon deep UV exposure and the second mechanism follows a free radical promoted cationic polymerization upon visible light illumination. The crosslinking and cleavage kinetics of the photodegradable epoxy networks are characterized by spectroscopic techniques. In thin films, the UV induced increase in solubility is confirmed by sol-gel analysis and used for the fabrication of positive tone photoresists. Patterned films are obtained by photolithographic processes and microscopic analyses reveal that the resists provide a resolution of 4 μm and a good contrast behavior. Graphical abstract: Highlights: Photoinduced cationic curing of epoxy monomers with photolabile o -NBE groups. Initiation proceeds by direct or sensitized photolysis of a photoacid generator. Thermal post-curing step is required for efficient curing of photolabile monomers. Controlled photocleavage of covalent links is evidenced by sol-gel analysis. Photocleavage enables preparation of positive tone patterns with good resolution.